Recent Near-surface Temperature Trends in the Antarctic Peninsula from Observed, Reanalysis and Regional Climate Model Data - Bozkurt, Deniz; Bromwich, David H.; Carrasco Cerda, Jorge Fernando; Hines, Keith M.; Maureira, Juan Carlos; Rondanelli, Roberto (My University, 2020)
This study investigates the recent near-surface temperature trends over the Antarctic Peninsula. We make use of available surface observations, ECMWF's ERA5 and its predecessor ERA-Interim, as well as numerical simulations, allowing us to contrast different data sources. We use hindcast simulations performed with Polar-WRF over the Antarctic Peninsula on a nested domain configuration at 45 km (PWRF-45) and 15 km (PWRF-15) spatial resolutions for the period 1991-2015. In addition, we include hindcast simulations of KNMI-RACMO21P obtained from the CORDEX-Antarctica domain (similar to 50 km) for further comparisons. Results show that there is a marked windward warming trend except during summer. This windward warming trend is particularly notable in the autumn season and likely to be associated with the recent deepening of the Amundsen/Bellingshausen Sea low and warm advection towards the Antarctic Peninsula. On the other hand, an overall summer cooling is characterized by the strengthening of the Weddell Sea low as well as an anticyclonic trend over the Amundsen Sea accompanied by northward winds. The persistent cooling trend observed at the Larsen Ice Shelf station is not captured by ERA-Interim, whereas hindcast simulations indicate that there is a clear pattern of windward warming and leeward cooling. Furthermore, larger temporal correlations and lower differences exhibited by PWRF-15 illustrate the existence of the added value in the higher spatial resolution simulation.
Keywords: dynamical downscaling; cloud computing; added value; reanalysis; amundsen; bellingshausen sea; weddell sea; temperature trend